417 Multi-chamber speckle tracking imaging and diagnostic value of left atrial strain in cardiac amyloidosis. (8th December 2021) - Aimo, Alberto; Fabiani, Iacopo; Giannoni, Alberto; Mandoli, Giulia Elena; Pastore, Maria Concetta; Vergaro, Giuseppe; Spini, Valentina; Chubuchny, Vladyslav; Pasanisi, Emilio Maria; Petersen, Christina; Poggianti, Elisa; Taddei, Claudia; et al.
Abstract: Aims: Amyloid deposits in all cardiac chambers, impairing their function. We investigated for the first time if a speckle-tracking echocardiography (STE) analysis extended to all four chambers might hold additive diagnostic value for CA and its subtypes [amyloid transthyretin (ATTR-) and light-chain (AL)-CA]. Methods and results: We evaluated 423 consecutive patients undergoing a diagnostic workup for CA in two referral centres from 2015 to 2020. CA was diagnosed in 261 patients (62%; ATTR-CA, n = 144, 34%; AL-CA, n = 117, 28%). Patients with CA had an impaired function of all cardiac chambers, particularly those with ATTR-CA. Peak left atrial longitudinal strain (LA-PALS) was the only STE parameter that predicted CA and ATTR-CA independent of laboratory and standard echocardiographic variables (Model 1). It also predicted ATTR-CA among patients with unexplained hypertrophy regardless of a diagnostic score (IWT score). Patients with either LA-PALS or LA-peak atrial contraction strain (PACS) in the first quartile (LA-PALS <6.65% or LA-PACS <3.62%) had an almost 4-fold higher likelihood of CA and ATTR-CA regardless of Model 1. Among patients with unexplained hypertrophy, those with LA-PALS or LA-PACS in the first quartile had an almost 9-fold higher likelihood of ATTR-CA irrespective of Model 1, and a 2-fold higher likelihood of ATTR-CA beyond the IWT score. Conclusions: STE measures of all two chambers are abnormal in patients with CA, particularly in those with ATTR-CA. LA strain holds independent diagnostic significance. Among patients screened for CA, those with LA-PALS <6.65% and/or LA-PACS <3.62% have a high likelihood of CA and ATTR-CA.